Registers in Beauty V-Logs - Ekgoan Susanti Utami; Mytha Candria (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
Beauty v-log is one of popular v-logs on YouTube. It also provides many registers but none of the other researchers conduct research on beauty v-logs registers. Thus, I attempt to discover and to explain the registers in beauty v-logs and the semantic change of registers in the beauty v-logs. There are three beauty v-loggers who were analyzed, namely Wayne Goss, Tati, and Angie HotandFlashy. They are native speaker of English. The beauty v-logs are audio-video formats which were uploaded in 2019. To collect the data, I used a non-participatory observation method and a note taking method. To analyze the data, I used a referential method. The result shows that there are fourteen registers have undergone semantic change which can be classified into three namely, metaphor, specialization, and generalization. Semantic change which mostly occurs metaphor because the meanings of the beauty v-logs registers transfer from different domains onto beauty domain.Keywords: registers; beauty v-log; beauty vlogger; semantic change